Czochralski method for preparing calcium fluoride crystal with high laser damage resistance
By doping with strontium ions and trace lithium ions combined with gradient temperature control technology, the problem of calcium fluoride crystals being easily damaged by high-power lasers was solved, and calcium fluoride crystals with high resistance to laser damage were prepared to meet the needs of high-end applications.
Patent Information
- Application Number
- CN202511125748.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-09-23
AI Technical Summary
Calcium fluoride crystals prepared by the existing pulling method are easily damaged under high-power laser irradiation, and traditional doping methods lead to lattice expansion and degradation of optical performance, making it difficult to meet the needs of high-end applications.
By doping with strontium ions and trace lithium ions combined with gradient temperature control technology, the temperature gradient of the melt-crystal interface is precisely controlled, growth defects are reduced, and the uniformity of crystal components is optimized. The lattice rigidity is enhanced by strontium ions, and the charge defects are compensated by lithium ions, thereby improving the resistance to laser damage.
The prepared calcium fluoride crystal has a laser damage threshold of 3.5 to 4.7 J/cm2 at a wavelength of 193 nm, significantly improving the optical performance and mechanical stability, meeting the needs of long-term high-power laser operation.
Smart Images

Figure CN120683614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of crystal technology, in particular to a method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method. Background Art
[0002] Calcium fluoride crystal is an important optical material with excellent optical properties. It can provide high transmittance in the ultraviolet to mid-infrared band. It is the preferred material for the light source of excimer laser lithography machines. Its high laser durability and stable refractive index characteristics enable it to play a key role in laser systems.
[0003] Natural calcium fluoride was first used as an optical component, such as microscope objectives and spectrometer prisms, due to its wide-band light transmittance. However, natural crystals have many defects and cannot meet high-precision requirements. With the development of crystal growth techniques such as the Czochralski method and the crucible-drop method, the artificial synthesis of calcium fluoride crystals has been industrialized. The Czochralski method can produce large-sized, high-optical-quality single crystals, promoting its application in lasers, photolithography and other fields. Calcium fluoride is a soft and brittle material that is easily damaged by high-power laser irradiation. Ion doping can increase the laser damage threshold, making its application in deep ultraviolet lithography and high-energy lasers possible.
[0004] Chinese patent publication number CN116377580A discloses a method for reducing the cleavage properties of calcium fluoride crystals by doping with rare earth ions. Yttrium ions or trivalent lanthanide ions (lanthanum to lutetium) are used as doping sources to produce calcium fluoride crystals with low cleavage properties. Yttrium ions or trivalent lanthanide ions (lanthanum to lutetium) have different radii than calcium ions, resulting in size differences. Therefore, doping with either a single ion or multiple ions can cause lattice expansion in the calcium fluoride crystal, creating vacancy defects and affecting optical properties.
[0005] A Chinese patent with the authorization number CN115537911B discloses a method and apparatus for preparing large-sized crystals by the Czochralski method. This invention uses the Czochralski method to prepare large-sized calcium fluoride crystals, emphasizing the influence of temperature on crystal growth, as well as its impact on the quality and performance of the crystals. During the traditional Czochralski method, the temperature gradient at the interface between the crystal and the melt is uneven, which can easily lead to lattice stress concentration and the formation of dislocations. When the crystal cools, the difference in thermal contraction exacerbates the internal stress and causes cracking. Impurities, volatiles, or tiny particles of crucible material that are not completely dissolved in the melt are easily captured by the growth interface, forming inclusions or bubbles, which reduce the optical uniformity of the crystal. For doped crystals, the convection and diffusion of solutes in the melt are significantly affected by the pulling speed and rotation speed. If the parameters are not properly controlled, it is easy to cause a doping concentration gradient along the axial or radial direction of the crystal, causing uneven refractive index and affecting the optical performance. Summary of the Invention
[0006] The present invention aims to provide a method for preparing calcium fluoride crystals with high laser damage resistance by a Czochralski method. The calcium fluoride crystals are doped with strontium ions and trace amounts of lithium ions, and their laser damage threshold can reach 3.5 to 4.7 J / cm 2 , with good resistance to laser damage, and is suitable for long-term high-power laser operation scenarios. Strontium ion doping can significantly improve the optical properties, mechanical stability and laser damage resistance of calcium fluoride crystals, but the size difference between strontium ions and calcium ions will cause local lattice expansion of the crystal, forcing the surrounding negative ions to deviate from the equilibrium position and form fluoride ion vacancies. The radius of lithium ions is small, and the charge compensation mechanism and defects can be coordinated to optimize the optical properties, thermal stability and laser damage resistance of strontium ion-doped calcium fluoride crystals. The calcium fluoride crystal adopts the pulling method combined with gradient temperature control technology to control the heating rate of each stage, accurately control the melt-crystal interface stability, reduce growth defects, optimize the uniformity of crystal components, reduce macroscopic defects, improve the optical properties of the crystal, and meet high-end applications.
[0007] To achieve the above objectives, the present application provides a method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method, comprising:
[0008] Step S1, mixing a calcium fluoride raw material, a strontium fluoride raw material and a lithium fluoride raw material, fully grinding and drying to obtain a mixed raw material;
[0009] Step S2: Place the mixed raw materials into a crucible, polish the surface of the seed crystal, fix it to the lower end of the seed crystal rod, adjust the position of the seed crystal to above the crucible, 10 to 30 mm away from the raw material surface, close the furnace chamber, and introduce inert gas;
[0010] Step S3, starting the heating system, adjusting the crucible rotation speed, gradually heating to a preset temperature, keeping the temperature, then lowering the seed crystal rod until the seed crystal contacts the melt, performing Czochralski method seed crystal directional growth, and obtaining a crystal blank;
[0011] Step S4: After the crystal blank is cooled to room temperature, the crystal surface is cleaned and annealed to obtain calcium fluoride crystals.
[0012] Preferably, in step S1, based on the mass of calcium fluoride, the added amount of the strontium fluoride raw material is (5-13) mg / kg, and the added amount of the lithium fluoride raw material is (0.1-1) mg / kg.
[0013] Preferably, in step S1, the drying temperature is 100-200° C., and the drying time is 2-4 hours.
[0014] Preferably, in step S2, the seed crystal is a cuboid of 7 mm × 7 mm × (50-70 mm),
[0015] Preferably, in step S3, the crucible rotates at a speed of 30 to 60 rpm.
[0016] Preferably, in step S3, the preset temperature is 1420-1460°C.
[0017] Preferably, in step S3, the gradient heating program is: heating to 1000°C at a rate of 10-15°C / h in the low temperature stage, heating to 1300°C at a rate of 5-10°C / h in the medium temperature stage, and heating to 1420-1460°C at a rate of 1-5°C / h in the high temperature stage; and the insulation time is 12-24h.
[0018] Preferably, in step S3, the speed of lowering the seed rod until the seed crystal contacts the melt is 5-10 mm / min, the crucible rotation speed is 5-10 rpm, the lifting rod rotation speed is 1-2 rpm, the heating rate is 0.2-0.5°C / min, and maintained for 5-10 minutes.
[0019] Preferably, in step S3, during the seeding stage of the Czochralski method seed crystal directional growth, the heating rate is regulated to be 0.5-1°C / h, the crucible rotation speed is 5-10 rpm, and the pulling rod rotation speed is 1-2 rpm, and the entire process is maintained for 30-60 min.
[0020] Preferably, in step S3, in the directional growth of the seed crystal by the pulling method, in the necking stage, the total pulling length is 50 to 80 mm, and the pulling rod rotation speed is 5 to 10 rpm; the heating rate in the initial stage is 1 to 2°C / h, the pulling speed is 0.3 to 0.5 mm / min, and the pulling length is 30 to 50 mm; the heating rate in the middle and late stages is 0.3 to 0.5°C / h, the pulling speed is 0.1 to 0.3 mm / min, and the pulling length is 20 to 30 mm.
[0021] Preferably, in step S3, in the directional growth of the seed crystal by the Czochralski method, in the shoulder expansion stage, after two shoulder expansions, the crystal diameter increases from 10 mm to the target size of 150-200 mm; the target diameter of the first shoulder expansion is 30-50 mm, the shoulder height is 20-50 mm, the cooling rate is 0.5-1°C / h, and the pulling speed is 0.5-1 mm / min; the target diameter of the second shoulder expansion is 150-200 mm, the shoulder height is 30-60 mm, the cooling rate is 0.5-1°C / h, and the pulling speed is 0.3-0.8 mm / min; when approaching the target diameter, the heating rate is adjusted to 0.1-0.5°C / h and maintained for 0.5-1 h.
[0022] Preferably, in step S3, in the directional growth of the seed crystal by the Czochralski method, in the equal-diameter growth stage, the target growth height is 300-500 mm, the crucible rotation speed is adjusted to 5-10 rpm, the heating rate is adjusted to 0.5-1°C / h, the pulling speed in the initial stage is 1-1.5 mm / min, the pulling height is 200-400 mm, the heating is terminated in the final stage, and the pulling speed is 1-3 mm / min.
[0023] Preferably, in step S4, the annealing temperature is 800-1100° C., the annealing heating rate is 50-100° C. / h, the holding time is 10-24h, and the cooling rate is 10-50° C. / h.
[0024] Compared with the prior art, the beneficial effects of the present invention are embodied in:
[0025] (1) The calcium fluoride crystals prepared by the present invention are doped with strontium ions and a trace amount of lithium ions. The laser damage threshold of the crystals doped with different strontium ion and lithium ion concentrations can reach 3.5 to 4.9 J / cm at a wavelength of 193 nm. 2 . Strontium ions can efficiently replace calcium ions in the crystal lattice. The introduction of strontium ions will enhance the rigidity of the crystal lattice, reduce the amplitude of lattice vibration, reduce the light absorption caused by lattice vibration, and improve stability. Although the radius of strontium ions is close to that of calcium ions, and the charge is balanced, theoretically no charge compensation is required, but the size difference between strontium ions and calcium ions will still cause the crystal lattice to expand locally, forcing the surrounding negative ions to deviate from the equilibrium position, forming fluoride ion vacancies to relieve stress. These vacancy defects will become weak points for laser damage. Lithium ions have a smaller radius and are difficult to directly replace calcium ions. They are mainly filled in the lattice gaps. Therefore, lithium ions are doped to fill in fluorine vacancies, neutralize defect charges, reduce the scattering and absorption of light by charged defects, and thus improve transmittance and laser damage threshold.
[0026] (2) The present invention improves upon the traditional Czochralski method by precisely controlling the temperature gradient from the melt to the crystal to optimize crystal quality. The traditional Czochralski method can easily cause impurities or bubbles in the melt to be drawn into the crystal, forming inclusions, or cause dislocation proliferation due to uneven local supercooling. By setting a continuous, controllable temperature gradient from the melt surface to the crystal growth zone, the solid-liquid interface can be stabilized in a near-planar state, avoiding local component segregation caused by melt convection, reducing impurity aggregation, lowering thermal stress inside the crystal, and reducing dislocations and cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a physical picture of calcium fluoride crystals with high laser damage resistance prepared by the pulling method.
[0028] Figure 2 The XRD diffraction patterns of the calcium fluoride crystals prepared in Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0029] The following examples are only used to more clearly illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.
[0030] The main compounds used in the examples and comparative examples were all commercially available products and were not subjected to any further purification treatment.
[0031] Example 1
[0032] A method for preparing calcium fluoride crystals with high laser damage resistance by a Czochralski method comprises:
[0033] Step S1: 1 kg of calcium fluoride powder, 5 mg of strontium fluoride powder and 0.1 mg of lithium fluoride powder are mixed, fully ground, and dried at 100° C. for 4 h to obtain a mixed raw material.
[0034] Step S2: Place the mixed raw materials into a crucible, cut the seed crystal into a 7 mm × 7 mm × 50 mm cuboid, polish the surface, and fix it to the lower end of the seed crystal rod. Adjust the position of the seed crystal to above the crucible, 10 to 30 mm away from the raw material surface, close the furnace chamber, and introduce inert gas.
[0035] Step S3: Start the heating system, adjust the crucible rotation speed to 30 rpm, and heat the mixture to 1000°C at a rate of 10°C / h, then gradually increase the temperature to 1300°C at a rate of 5°C / h, and finally to 1420°C at a rate of 1°C / h. Hold the mixture for 24 hours. Adjust the crucible rotation speed to 5 rpm, the lifting rod rotation speed to 1 rpm, and the heating rate to 0.2°C / min. Lower the seed rod at a rate of 5 mm / min until the seed crystal contacts the melt, and maintain this temperature for 10 minutes.
[0036] During the seeding stage, the heating rate was adjusted to 0.5°C / h, the crucible rotation speed was maintained at 5 rpm, and the lifting rod rotation speed was maintained at 1 rpm for 60 min.
[0037] During the necking stage, the heating rate was adjusted to 1°C / h, the rotation speed of the pulling rod was 5rpm, and the pulling speed was 0.3mm / min. The crystal was pulled upward until the length reached 30mm. Then the heating rate was adjusted to 0.3°C / h, the pulling speed was 0.1mm / min, and the crystal was continued to be pulled upward until the length reached 50mm.
[0038] During the shoulder expansion stage, the crucible temperature was adjusted to cool down at 0.5℃ / h, and the pulling speed was adjusted to 0.5mm / min. The crystal was pulled upward until its diameter increased to 30mm. The shoulder height of this section was 20mm. The pulling speed was reduced to 0.3mm / min. The crystal was pulled until its diameter reached 150mm. The shoulder height of this section was 30mm. After reaching the target diameter, the temperature was adjusted to rise at 0.1℃ / h and maintained for 0.5h.
[0039] During the equal-diameter growth stage, the crucible rotation speed was adjusted to 5 rpm, the heating rate was 0.5 °C / h, the pulling speed was 1 mm / min, and the pulling was 200 mm. Then the heating was stopped, the pulling speed was adjusted to 1 mm / min, and the material was pulled to the target height of 300 mm.
[0040] Step S4: After the crystal blank is cooled to room temperature, clean the crystal surface, heat it to 800℃ at a rate of 50℃ / h for annealing for 24h, and then cool it to room temperature at a rate of 10℃ / h to obtain calcium fluoride crystals. Figure 1 shown.
[0041] Example 2
[0042] A method for preparing calcium fluoride crystals with high laser damage resistance by a Czochralski method comprises:
[0043] Step S1: 1 kg of calcium fluoride powder, 8 mg of strontium fluoride powder and 0.4 mg of lithium fluoride powder are mixed, fully ground, and dried at 120° C. for 3 h to obtain a mixed raw material.
[0044] Step S2: Place the mixed raw materials into a crucible, cut the seed crystal into a 7 mm × 7 mm × 60 mm cuboid, polish the surface, and fix it to the lower end of the seed crystal rod. Adjust the position of the seed crystal to above the crucible, 10 to 30 mm away from the raw material surface, close the furnace chamber, and introduce inert gas.
[0045] Step S3: Start the heating system, adjust the crucible rotation speed to 40 rpm, and heat the mixture to 1000°C at a rate of 12°C / h, then gradually increase the temperature to 1300°C at a rate of 6°C / h, and finally to 1440°C at a rate of 3°C / h. Hold the mixture for 20 hours. Adjust the crucible rotation speed to 10 rpm, the lifting rod rotation speed to 2 rpm, the heating rate to 0.3°C / min, and lower the seed rod at a rate of 10 mm / min until the seed crystal contacts the melt. Hold the mixture for 5 minutes.
[0046] During the seeding stage, the heating rate was adjusted to 0.6°C / h, the crucible rotation speed was maintained at 10 rpm, and the lifting rod rotation speed was maintained at 2 rpm for 50 min.
[0047] During the necking stage, the heating rate was adjusted to 2°C / h, the rotation speed of the pulling rod was 10rpm, and the pulling speed was 0.4mm / min. The crystal was pulled upward until the length reached 40mm. Then the heating rate was adjusted to 0.4°C / h, the pulling speed was 0.2mm / min, and the crystal was continued to be pulled upward until the length reached 60mm.
[0048] During the shoulder expansion stage, the crucible temperature was adjusted to cool down at 0.6℃ / h, and the pulling speed was adjusted to 0.6mm / min. The crystal was pulled upward until its diameter increased to 40mm. The shoulder height of this section was 30mm. The pulling speed was reduced to 0.5mm / min. The crystal was pulled until its diameter reached 160mm. The shoulder height of this section was 40mm. After reaching the target diameter, the temperature was adjusted to rise at 0.3℃ / h and maintained for 1h.
[0049] During the equal-diameter growth stage, the crucible rotation speed was adjusted to 10 rpm, the heating rate was 0.6°C / h, the pulling speed was 1.5 mm / min, and the pulling was 300 mm. Then the heating was stopped, the pulling speed was adjusted to 2 mm / min, and the pulling was carried out to the target height of 400 mm.
[0050] Step S4: After the crystal blank is cooled to room temperature, clean the crystal surface, heat it to 850℃ at a rate of 70℃ / h for annealing for 18h, and then cool it to room temperature at a rate of 20℃ / h to obtain calcium fluoride crystals. Figure 1 shown.
[0051] Example 3
[0052] A method for preparing calcium fluoride crystals with high laser damage resistance by a Czochralski method comprises:
[0053] Step S1: 1 kg of calcium fluoride powder, 13 mg of strontium fluoride powder and 1 mg of lithium fluoride powder are mixed, fully ground, and dried at 200° C. for 2 h to obtain a mixed raw material.
[0054] Step S2: Place the mixed raw materials into a crucible, cut the seed crystal into a 7 mm × 7 mm × 70 mm cuboid, polish the surface, and fix it to the lower end of the seed crystal rod. Adjust the position of the seed crystal to above the crucible, 10 to 30 mm away from the raw material surface, close the furnace chamber, and introduce inert gas.
[0055] Step S3: Start the heating system, adjust the crucible rotation speed to 60 rpm, and heat the mixture to 1000°C at a rate of 15°C / h, then gradually increase the temperature to 1300°C at a rate of 10°C / h, and finally to 1460°C at a rate of 5°C / h. Hold the mixture for 12 hours. Adjust the crucible rotation speed to 10 rpm, the lifting rod rotation speed to 2 rpm, the heating rate to 0.5°C / min, and lower the seed rod at a rate of 10 mm / min until the seed crystal contacts the melt. Hold the mixture for 5 minutes.
[0056] During the seeding stage, the heating rate was adjusted to 1°C / h, the crucible rotation speed was maintained at 10 rpm, and the lifting rod rotation speed was maintained at 1 rpm for 30 min.
[0057] During the necking stage, the heating rate was adjusted to 1°C / h, the rotation speed of the pulling rod was 10 rpm, and the pulling speed was 0.5 mm / min. The crystal was pulled upward until the length reached 50 mm. Then the heating rate was adjusted to 0.5°C / h, the pulling speed was 0.3 mm / min, and the crystal was continued to be pulled upward until the length reached 80 mm.
[0058] During the shoulder expansion stage, the crucible temperature was adjusted to cool down at 1°C / h, and the pulling speed was adjusted to 1mm / min. The crystal was pulled upward until its diameter increased to 50mm. The shoulder height of this section was 50mm. The pulling speed was reduced to 0.8mm / min. The crystal was pulled until its diameter reached 200mm. The shoulder height of this section was 60mm. After reaching the target diameter, the temperature was adjusted to rise at 0.5°C / h and maintained for 0.5h.
[0059] During the equal-diameter growth stage, the crucible rotation speed was adjusted to 10 rpm, the heating rate was 1°C / h, the pulling speed was 1.5 mm / min, and the pulling was 400 mm. Then the heating was stopped, the pulling speed was adjusted to 3 mm / min, and the pulling was carried out to the target height of 500 mm.
[0060] Step S4: After the crystal blank is cooled to room temperature, clean the crystal surface, heat it to 1000℃ at a rate of 100℃ / h for 10h, and then cool it to room temperature at a rate of 50℃ / h to obtain calcium fluoride crystals. Figure 1 shown.
[0061] Comparative Example 1
[0062] A calcium fluoride crystal with high resistance to laser damage, the preparation method of which is different from that of Example 3 in that lithium fluoride is not added in step S1.
[0063] XRD diffraction data of metal ion doped calcium fluoride crystals, such as Figure 2As shown. It is known that the diffraction peak of the
[111] crystal plane of pure calcium fluoride crystal is about 28.3°, and the scattering superposition effect is the strongest; the diffraction peak of the
[220] crystal plane is about 47.1°, with medium intensity. The diffraction peak of the
[111] crystal plane of the calcium fluoride crystal prepared in Example 1 appears at 28.23°, and the diffraction peak of the
[220] crystal plane appears at 47.03°. The diffraction peak of the
[111] crystal plane of the calcium fluoride crystal prepared in Example 2 appears at 28.20°, and the diffraction peak of the
[220] crystal plane appears at 47.04°. The diffraction peak of the
[111] crystal plane of the calcium fluoride crystal prepared in Example 3 appears at 28.16°, and the diffraction peak of the
[220] crystal plane appears at 46.86°. The radius of strontium ions is slightly larger than that of calcium ions. Therefore, doping causes the lattice of calcium fluoride crystals to expand, causing the diffraction peaks of the
[111] and
[220] crystal planes to shift toward low angles (i.e., shift to the left). However, the crystal is also doped with a small amount of lithium ions, and the radius of lithium ions is significantly smaller than that of calcium ions and strontium ions. Therefore, when lithium ions enter the lattice, they can only preferentially fill the lattice gaps created during the strontium ion doping process, offsetting the lattice expansion caused by strontium ions and alleviating lattice distortion. Therefore, the shift of the diffraction peaks of strontium ion-doped calcium fluoride crystals toward low angles is weakened.
[0064] Performance testing:
[0065] (1) Optical uniformity: Process the crystal sample into The optical uniformity of the sample was measured using a Fizeau interferometer (zygoMST, USA).
[0066] (2) Transmittance: Process the crystal into The transmittance of the crystal at 248 nm was tested using a universal spectrophotometer (Agilent Cary7000).
[0067] (3) Laser damage threshold test: Using an ultraviolet laser damage platform, by gradually increasing the laser power density, observe whether damage (such as cracks, cleavage, etc.) occurs on the surface or inside the crystal, and record the lowest laser power density that causes damage at a wavelength of 193nm.
[0068] Table 2 Crystal performance test data
[0069] Sample number <![CDATA[Optical uniformity (×10 -6 )]]> Transmittance (%) <![CDATA[Laser damage threshold (J / cm 2 )]]> Example 1 6.45 92.75 3.5 Example 2 6.72 93.16 3.9 Example 3 7.05 93.22 4.7 Comparative Example 1 12.85 90.05 3.3
[0070] According to the data in Table 2, the optical uniformity and transmittance of the calcium fluoride crystals prepared in Examples 1 to 3 are significantly higher than those prepared in Comparative Example 1. The laser damage threshold of the crystal prepared in Example 1 is 3.5 J / cm 2 The laser damage threshold of the crystal prepared in Example 2 is 3.9 J / cm 2 The laser damage threshold of the crystal prepared in Example 3 is 4.7 J / cm2 The laser damage threshold of the crystal prepared in comparative example 1 is 3.3 J / cm 2 The laser resistance of the crystals prepared in Examples 1 to 3 is significantly higher than that in Comparative Example 1.
[0071] In Comparative Example 1, no lithium ions were added, and only a single strontium ion was used for doping. Due to the difference in radius, the calcium fluoride crystals suffered lattice distortion. To alleviate the stress caused by the distortion, the crystals adjusted the atomic arrangement by forming fluorine vacancies. Due to the interaction between vacancies, isolated fluorine vacancies tended to move closer to each other, forming vacancy clusters, which aggravated light scattering. Therefore, the optical uniformity, transmittance, and laser damage threshold of the calcium fluoride crystals prepared in Comparative Example 1 differed significantly from those of the other groups.
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method, characterized in that: include: Step S1, mixing a calcium fluoride raw material, a strontium fluoride raw material and a lithium fluoride raw material, fully grinding and drying to obtain a mixed raw material; Step S2: Place the mixed raw materials into a crucible, polish the surface of the seed crystal, fix it to the lower end of the seed crystal rod, adjust the position of the seed crystal to above the crucible, 10 to 30 mm away from the raw material surface, close the furnace chamber, and introduce inert gas; Step S3, starting the heating system, adjusting the crucible rotation speed, gradually heating to a preset temperature, maintaining the temperature, then lowering the seed crystal rod until the seed crystal contacts the melt, performing Czochralski seed crystal directional growth, and obtaining a crystal blank; Step S4: After the crystal blank is cooled to room temperature, the crystal surface is cleaned and annealed to obtain calcium fluoride crystals.
2. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S1, based on the mass of calcium fluoride, the added amount of the strontium fluoride raw material is (5-13) mg / kg, and the added amount of the lithium fluoride raw material is (0.1-1) mg / kg; the drying temperature is 100-200° C., and the drying time is 2-4 hours.
3. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S2, the seed crystal is a cuboid of 7 mm×7 mm×(50-70 mm).
4. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S3, the crucible rotation speed is 30-60 rpm; the preset temperature is 1420-1460°C; the gradient heating program is: heating to 1000°C at 10-15°C / h in the low temperature stage, heating to 1300°C at 5-10°C / h in the medium temperature stage, and heating to 1420-1460°C at 1-5°C / h in the high temperature stage; and the insulation time is 12-24 hours.
5. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S3, the speed of lowering the seed rod until the seed crystal contacts the melt is 5-10 mm / min, the crucible rotation speed is 5-10 rpm, the lifting rod rotation speed is 1-2 rpm, the heating rate is 0.2-0.5°C / min, and the temperature is maintained for 5-10 minutes.
6. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S3, during the seeding stage of the Czochralski method seed crystal directional growth, the heating rate is regulated to be 0.5-1°C / h, the crucible rotation speed is 5-10 rpm, and the pulling rod rotation speed is 1-2 rpm. The whole process is maintained for 30-60 minutes.
7. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S3, during the directional growth of the seed crystal by the pulling method, in the necking stage, the total pulling length is 50 to 80 mm, and the pulling rod rotation speed is 5 to 10 rpm; the heating rate in the initial stage is 1 to 2°C / h, the pulling speed is 0.3 to 0.5 mm / min, and the pulling length is 30 to 50 mm; the heating rate in the middle and late stages is 0.3 to 0.5°C / h, the pulling speed is 0.1 to 0.3 mm / min, and the pulling length is 20 to 30 mm.
8. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S3, during the directional growth of the seed crystal by the Czochralski method, in the shoulder expansion stage, after two shoulder expansions, the crystal diameter increases from 10 mm to the target size of 150 to 200 mm; the target diameter of the first shoulder expansion is 30 to 50 mm, the shoulder height is 20 to 50 mm, the cooling rate is 0.5 to 1°C / h, and the pulling speed is 0.5 to 1 mm / min; the target diameter of the second shoulder expansion is 150 to 200 mm, the shoulder height is 30 to 60 mm, the cooling rate is 0.5 to 1°C / h, and the pulling speed is 0.3 to 0.8 mm / min; after reaching the target diameter, the heating rate is adjusted to 0.1 to 0.5°C / h and maintained for 0.5 to 1 hour.
9. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S3, in the directional growth of the seed crystal by the Czochralski method, in the equal-diameter growth stage, the target growth height is 300-500 mm, the crucible rotation speed is adjusted to 5-10 rpm, the heating rate is adjusted to 0.5-1°C / h, the pulling speed in the initial stage is 1-1.5 mm / min, the pulling height is 200-400 mm, and the heating is terminated in the final stage, and the pulling speed is 1-3 mm / min.
10. The method for preparing calcium fluoride crystals with high resistance to laser damage by a Czochralski method according to claim 1, characterized in that: In step S4, the annealing temperature is 800-1100° C., the annealing heating rate is 50-100° C. / h, the holding time is 10-24 hours, and the cooling rate is 10-50° C. / h.